2013
DOI: 10.1364/ol.38.001509
|View full text |Cite
|
Sign up to set email alerts
|

Soft x-ray low-pass filter with a square-pore microchannel plate

Abstract: A type of low-pass filter devices for soft x rays is investigated by using a microchannel plate (MCP) of small channels with square cross section. The measured transmission spectra on the Beijing Synchrotron Radiation Facility showed that the MCP has excellent bandpass effects below 1.5 keV by grazing incidence and internal multireflections. Combined with filters, the MCP energy bandwidth can be narrowed to 100 eV. In contrast to bandpass made of planar mirrors, the MCP has a much smaller size and better bandp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Apart from this, we have also calculated the angular distribution of emitted harmonics [refer to Fig. 4] and it is observed that particular harmonics are emitted along specific directions, which in principle is useful to tune the detectors to utilize the radiation of a particular energy [51]. The generation and application of the attosecond pulses is interesting in its own right and in this work, we were able to obtain the attosecond pulses ranging from ∼80-276 as with good spatial and temporal coherence properties, depending on the incident laser intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this, we have also calculated the angular distribution of emitted harmonics [refer to Fig. 4] and it is observed that particular harmonics are emitted along specific directions, which in principle is useful to tune the detectors to utilize the radiation of a particular energy [51]. The generation and application of the attosecond pulses is interesting in its own right and in this work, we were able to obtain the attosecond pulses ranging from ∼80-276 as with good spatial and temporal coherence properties, depending on the incident laser intensity.…”
Section: Discussionmentioning
confidence: 99%
“…The MCP transmission in the XUV spectral region has been measured in [19] to be as high as 60% for photon energies from 50 eV to 1.5 keV, reaching the upper limit set by the MCP opening ratio. It is reasonable to assume that the transmission should be the same for even higher energy photons due to their decreasing wavelengths.…”
mentioning
confidence: 88%
“…It is reasonable to assume that the transmission should be the same for even higher energy photons due to their decreasing wavelengths. The measurement in [19] was done by placing an XUV photodiode 1 mm away from the MCP, indicating that the total transmission was measured. However, only the zerothorder transmission is useful for studying ultrafast dynamics.…”
mentioning
confidence: 99%
“…Hence, generating a brilliant spot size is a challenging issue, but extremely important for a large class of experiments. Moreover, the continuously growing demand for low-emittance SR sources and XFELs requires new optical elements capable of focusing or shaping radiation as well as filtering or shifting the energy of the X-ray beam (Cao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…(Gao & Janssens, 2004). They can also be applied as a condenser in a soft X-ray microscope coupled to a plasma X-ray source (Cao et al, 2013). Furthermore, studies on the propagation of X-ray radiation inside MCPs are particularly interesting for improving the spot stability and for optimizing the characteristics of a soft X-ray beam, e.g.…”
Section: Introductionmentioning
confidence: 99%